2017
DOI: 10.14409/fa.v16i2.7014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Priming on Germination and Initial Growth of Melon Plants Under Salt Stress

Abstract: The objective of this work was to evaluate the effect of different osmotic agents and priming durations on the germination and initial growth of melon in salinity. The osmotic agents were NaCl and CaCl 2 and durations 2 and 4 days. First a response curve of germination to salinity was made. After priming the seeds were placed to germinate in a saline medium (14 dS m -1 ). The germination percentage was determined. The two treatments with the best results (NaCl and CaCl 2 2 days in both salts) were selected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The heatmap also demonstrates Pro accumulation under salt stress. Castañares et al [ 119 ] demonstrated significant Pro accumulation in melon under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…The heatmap also demonstrates Pro accumulation under salt stress. Castañares et al [ 119 ] demonstrated significant Pro accumulation in melon under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Perlakuan priming telah terbukti bermanfaat dalam invigorasi benih selama penyimpanan, selain itu juga dapat meningkatkan, mempercepat dan menyeragamkan perkecambahan serta pembentukan bibit, mengatasi atau mengurangi berbagai tipe dormansi, serta meningkatkan perkecambahan dan pembentukan bibit pada kondisi lingkungan yang tidak menguntungkan. Manfaat dari priming tidak terkhusus pada tahap perkecambahan saja, namun dapat berdampak pada fase selanjutnya, yaitu dengan meningkatkan tolensi terhadap perbedaan tekanan biotik dan abiotik (Castanares & Bouzo, 2017 Tabel 5 dan 6 menunjukkan tidak adanya beda nyata antara benih baru dengan benih lama, sedangkan benih lama kontrol dengan perlakuan terdapat beda nyata. Hal ini menunjukkan bahwa dari perlakuan memberikan nilai bobot segar dan bobot kering yang lebih tinggi daripada benih lama tanpa perlakuan.…”
Section: Hasil Dan Pembahasanunclassified